Habitat, morphology, population genetics and reproductive biology of hard clam (Bivalvia : Veneridae) from two locations in Sarawak - Hamli, Hadi (2015)
Biology and habitat characteristic of most common and abundance hard clam Meretrix spp. was investigated at two selected division of Sarawak namely Kuching and Betong from May 2013 to April 2014. Both areas comprised intertidal areas with sandy type sediment which able to support the growth of Meretrix spp. Environmental factor play important role to influence biology and physiology of Meretrix spp. for the present study. Habitat area for Meretrix spp. in the present study recorded the concentration of hydrogen ion (pH) range from 7.73–8.31, total dissolved solid 35.358–50.467 mg/L, salinity 22.5–31.8 psu, temperature 25.3–27.7 °C, turbidity 82.9–999 ntu, conductivity 3.473–4.683 S/cm, dissolved oxygen 3.74–5.58 mg/L, total rainfall 162.6–729.4 mm, ammonia 0.023–0.223 mg/L, nitrite 0.004–0.017 mg/L, nitrate 0.167–1.233 mg/L, phosphate 0.097–0.43 mg/L, total suspended solid 0.041–0.147 mg/L and chlorophyll a 0.419–0.147 μg/L. A total of 3 hard clam species identified based on morphological characteristic were Meretrix lyrata, M. meretrix and M. lusoria. Pallial sinus scar profile was the main morphological characteristic used for the differentiation of these 3 Meretrix spp. While, a total of 13 morphometric characteristics were used to differentiate the three species of Meretrix recorded from Sarawak. Significant differences (ANOVA, p<0.05) on 7 morphometric characteristics (SW; Shell Width, AL; Anterior Length, LCT; Length of Cardinal Tooth, AW; Anterior Adductor Scar Width, PW; Posterior Adductor Scar Width, PS; Pallial Sinus Open Scar and LL; Ligament Length) based on proportion ratio with SL (Shell Length) were found among three Meretrix species recorded. Variation among Meretrix shell characteristic also was strengthen by results from clustering analysis, Principal Component Analysis (PCA) and genetic characteristic. Genetic characteristic between M. lyrata, M. meretrix and M. lusoria were investigated based on universal marker cytochrome C oxidase subunit I (COI) with sequence LCO1490: 5’-ggtcaacaaatcataaagatattgg-3’ and HCO2198: 5’- taaacttcagggtgaccaaaaaatca-3’. Genetic characteristic between this Meretrix spp. was able to be distinguished through phylogenetic analysis. The result was crucial to support the morphology and morphometric characterization. However, the present study using molecular approach was unable to verify the species of Meretrix sp. Therefore, additional genetic approaches are needed for further verification. Present investigation on reproductive biology was able to determine the reproductive stages and spawning period of Meretrix lyrata within one year. Determination was made based on quantitative (Gonad Index and Condition Index) and qualitative approach (histological procedure). This study showed that the spawning period of M. lyrata is from May to September. Most of the M. lyrata in the studied samples undergoes continuous gonad development for 7 months from October 2013 to April 2014. This indicated M. lyrata only has one cycle of reproductive development in a year. Reproductive development of M. lyrata positively correlated to the abundance of phytoplankton in coastal area.